Pengaruh Motivasi Kerja dan Kedisiplinan Kerja terhadap Kinerja Pegawai UPT Puskesmas Seko - Tarae, Kurniati; Sundari, Ocky (Universitas Proklamasi 45, 2024)
This research aims to examine the influence of work motivation and work discipline on employee performance. The population of this study were all employees of the UPT Puskesmas Seko, North Luwu Regency, South Sulawesi Province. The sample for this research was 60 people. The analysis technique used to prove the hypotheses is multiple linear regression with data processing using Statistical Package for Social Science (SPSS) version 23 software. Based on testing, the research results show that work motivation has a significant effect on the performance of UPT Puskesmas Seko employees. The higher the encouragement or motivation given to employees the higher the employee's performance will be. Work motivation can be received from various aspects starting from the relationship between superiors and subordinates, work environment, salary, and facilities provided. Other findings show that work discipline has a significant effect on employee performance. The disciplined attitude of UPT Puskesmas Seko employees means they always comply with regulations and carry out their obligations as they should. Apart from that, work discipline can also help UPT Puskesmas Seko employees to understand work problems given by the leaders so that there are no employees who underestimate and violate regulations so that employee performance will be better.